2000
DOI: 10.1074/jbc.m005147200
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of an Equilibrium Intermediate in the Unfolding Pathway of an All β-Barrel Protein

Abstract: The guanidinium hydrochloride (GdnHCl)-induced unfolding of an all ␤-sheet protein, the human acidic fibroblast growth factor (hFGF-1), is studied using a variety of biophysical techniques including multidimensional NMR spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 38 publications
2
52
0
1
Order By: Relevance
“…These observations are suggestive of a molten-globule-like character of the I1 state; a similar type of molten-globule state was reported previously for human acidic fibroblast growth factor (hFGF-1) (47,48). The I2 state has substantial secondary structure and also shows weak ANS binding, which suggests that this state is a partly condensed state with a small solvent-accessible non-polar cluster.…”
Section: Discussionsupporting
confidence: 82%
“…These observations are suggestive of a molten-globule-like character of the I1 state; a similar type of molten-globule state was reported previously for human acidic fibroblast growth factor (hFGF-1) (47,48). The I2 state has substantial secondary structure and also shows weak ANS binding, which suggests that this state is a partly condensed state with a small solvent-accessible non-polar cluster.…”
Section: Discussionsupporting
confidence: 82%
“…The GdnHCl-induced unfolding of hFGF-1 is non-cooperative (38). GdnHCl-induced unfolding of hFGF-1 was monitored by steady-state fluorescence (based on the 350/308 nm fluorescence changes) and far UV CD (using ellipticity changes at 228 nm).…”
Section: Accumulation Of An Equilibrium Unfolding Intermediate State(s)mentioning
confidence: 99%
“…Middaugh and co-workers (36,37) showed that hFGF-1 exists in a partially structured state(s) that exhibits high affinity to bind to negatively charged phospholipid vesicles. Recently, Samuel et al (38) identified and characterized an obligatory partially unfolded intermediate state in the GdnHCl unfolding pathway of hFGF-1. In the present study, we investigate the structure and dynamic features of this obligatory intermediate state of hFGF-1 using a variety of techniques including multidimensional NMR.…”
mentioning
confidence: 99%
“…7, inset). The fluorescence of the lone tryptophan residue located at position 121 is significantly quenched in the native state of the protein (43)(44)(45)(46). This quenching effect is attributed to the presence of imidazole and pyrrole groups in the vicinity of the indole ring of the tryptophan (Trp-121) residue (31).…”
Section: Fig 6 Aggregation Induced By Pre-formed Fibrils (Formed Inmentioning
confidence: 99%